Assessment of discomfort in patients with cognitive failure in palliative care*. Issue 3 (3rd August 2015) - Ferraz Gonçalves, José António; Costa, Elisabete; Edra, Natércia; Gil, João; Martinho, Carla; Neves, Emília; Peixoto, Vânia; Rodrigues, Andreia; Silva, Margarida; Teixeira, Sara
Abstract: Objective: When cognitive impairment precludes patients' report of symptoms, it becomes necessary to use other means. The purpose of our study was to evaluate the validity of the method currently in use on our service. Method: Two members of the team simultaneously assessed the patient and independently recorded whether the patient showed signs of discomfort, and a third questioned patients with cognitive failure who maintained some ability to respond if something was bothering them. Results: Some 200 assessments were made of 116 patients. The kappa coefficient of agreement was 0.615. The sensitivity was 17% and specificity 99%. The positive predictive value was 88%, and the negative predictive value was 73%. Significance of Results: Due to the low sensitivity of this method, it cannot be recommended as a screening tool.